EFFECTS OF PRETREATMENT METHODS ON THE LIGNOCELLULOSIC COMPOSITION OF SALACCA MIDRIBS - Berlian Simanjuntak; Isabella Kristin Hotma Silalahi (BIOMA : Jurnal Ilmiah Biologi, 2026)
This study aims to determine the effect of pretreatment on hemicellulose, cellulose, and lignin content of Salacca midrib. Unlike previous studies, this study was designed to evaluate the effects of single-, double-, and triple-stage pretreatments on the sallaca midrib. The study was also designed to evaluate the differences in the physical and biological pretreatment methods. The pretreatments applied consist of physical, chemical, biological, physicochemical, chemical-biological, physical-biological, and physicochemical-biological pretreatments. Physical pretreatment is carried out in an autoclave at 121 °C, chemical pretreatment using Sodium Hydroxide (NaOH) 4%, and biological pretreatment using Debaryomyces hansenii. Based on the ANOVA test, the various pretreatment methods have a significant effect on lignocellulose content. The highest hemicellulose content was the chemical pretreatment at 34.13%, the cellulose content was the chemical pretreatment at 40.85%, and the highest lignin reduction was the physical-chemical-biological at 27.15%